HEALTH STATUS AND ITS EFFECTS ON DAILY MILK PRODUCTION IN SIMMENTAL COWS CONSIDERING KEY ANIMAL-RELATED FACTORS - Ljubojević, Boris; Steiner, Zvonimir; Gantner, Ranko; Potočnik, Klemen; Gantner, Vesna (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
This study analyzed the effect of mastitis on daily milk production parameters in Simmental cows, considering factors such as lactation stage, parity, and production level. After applying quality control measures, the final dataset consisted of 2,835,101 test-day records of dairy Simmental cows. The results showed that both subclinical and clinical mastitis negatively impacted milk yield and milk composition. Cows with subclinical mastitis had lower milk production compared to healthy cows, while those with clinical mastitis experienced even more significant losses. Mastitis also influenced milk quality, with increased fat and protein content and decreased lactose levels. The effects were more pronounced in cows in later stages of lactation and those with higher production levels. Early detection and intervention are critical to minimize milk production losses and maintain milk quality. Improving farm management practices, such as monitoring somatic cell counts and ensuring proper hygiene and nutrition, is essential for optimizing milk production and reducing economic losses.